BEEPS At-a-Glance 2013 : Armenia - Kisunko, Gregory (World Bank, Washington, DC, 2015)
The EBRD-World Bank Business Environment and Enterprise Performance Survey (BEEPS) is a joint initiative of the European Bank for Reconstruction and Development and the World Bank. The BEEPS has been carried out in five rounds: in 1999, 2002, 2005, 2008, and 2012/13 (the latest BEEPS in Russian Federation was conducted in 2011/12) and covers virtually all of the countries of Central and Eastern Europe and the former Soviet Union, as well as Turkey. The BEEPS covers a broad range of issues about the business environment, and this note presents some simple indicators for key areas.